(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2004)
Opinion was given by the doctors of Patna Medical college, Safdarjang Hospital and AIIMS in Gautam and Shilpi Jain’s death case. These opinions were interpreted by the CBI as under, which was reported in Hindustan Times on 07/08/2003, Patna edition. By going through the contents of the following subject matter, readers will find it useful to understand the significance of the opinions /subsequent opinions given by them.